Stress and well-being at the strategic level - Harms, Peter; Chang, Chu-Hsiang (Emerald Publishing, 2024)
Volume 21 of Research in Occupational Stress and Well Being focuses on stress and well-being as it pertains to strategic management and decision-making. In the past few decades, the strategic leadership of firms has been faced with unprecedented challenges in terms of technological changes, economic and political crises, and radical shifts in the workplace owing to health crises. These events have highlighted the need to understand the consequences of stress as a factor impacting strategic decisions. At the same time, firms are increasingly realizing the need to account for the stress and well-being of their employees, their customers, and their communities as factors influencing the ability of their businesses to flourish in a sustainable manner. Chapters in this volume cover a range of topics including: How stress and well-being can influence the decision-making and effectiveness of higher management teams. How organizational changes such as mergers/acquisitions or downsizing might impact the stress and well-being of both leaders and followers. Strategic initiatives that might directly or indirectly promote the well-being of organizational members or customers. CEO mental health and its consequences for strategy and organizational effectiveness. Strategic decision-making in times of crisis. Highlighting how both leader and follower stress and well-being can serve as antecedents and consequences of strategic actions and initiatives, or even be a core concern of strategic plans, Stress and Well-Being at the Strategic Level spotlights the importance of stress and well-being for organizations, their leaders, and the individuals who are impacted by their decisions.
Keywords: Strategic planning; Executives / Job stress; Decision making; Business & Economics; Strategic Planning; Business strategy; Aufsatzsammlung